Effects of sturgeon oil and reheating methods on the qualities of sturgeon surimi gels - Yuanxiu Liu; Xiaomo Guo; Tong Shi; Zhiyu Xiong; Li Yuan; Ruichang Gao (Food Science of Animal Products)
The addition of oil played a significant role in the gelling properties and flavor qualities of the ready-to-eat surimi gels. In order to investigate the effects of sturgeon oil and reheating methods on the qualities of sturgeon surimi gels, the prepared sturgeon surimi gels containing sturgeon oil (with the direct addition named SO and with the Pickering emulsion named PPE) were reheated by boiling, steaming, microwave, and frying, respectively. The gel properties, non-volatile and volatile flavor substances and digestibility were determined. Boiling and steaming made gels higher brightness value (L*) (82.07–84.16), with lower cooking loss (7.11%–8.83%), relatively intact protein network structures and strong protein digestibility. The greatest lipid oxidation of the sturgeon surimi gels was induced by frying, followed by microwave. Furthermore, the gels reheated by microwave showed the highest total flavor-presenting nucleotides, while the steamed ones had the highest total percentage of fresh and sweet amino acids. The addition of sturgeon oil (direct addition and Pickering emulsion) decreased the textural properties of the reheated gels, but significantly improved the L* and protein digestibility of boiled and steamed gels (P < 0.05). The gastric digestibility and gastrointestinal digestibility of the SO and PPE groups were 68.60%–76.33% and 80.69%–85.05%. Moreover, the addition of sturgeon oil also changed the ratio of non-volatile and volatile flavor compounds. Compared with the direct addition of sturgeon oil, the preparative Pickering emulsion was more conducive to the retention of better textural properties as well as the more flavor-presenting nucleotides and volatile flavor substances. The above results enrich the theory of quality difference of sturgeon surimi products caused by different reheating methods, and provide reference for the development of high-quality products.